(untitled) (Global Journal of Science Frontier Research, 2018)
Eleven rice genotypes were evaluated at 6 environments in Western Ethiopia during 2015 and 2016 main cropping season. The objective of the study was to determine the magnitude of genotype x environment interaction and performance stability in the rice genotypes. The study was conducted using a randomized complete design with 3 replications. Genotype x environment interaction and yield stability were estimated using the additive main effects and multiplicative interaction and site regression genotype plus genotype x environment interaction bi plot pooled analysis of variance for grain yield showed significant (P